2019
DOI: 10.1002/ecs2.2860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restoration on tree communities and carbon storage in rainforest fragments of the Western Ghats, India

Abstract: Ecological restoration is a leading strategy for reversing biodiversity losses and enhancing terrestrial carbon sequestration in degraded tropical forests. There have been few comprehensive assessments of recovery following restoration in fragmented forest landscapes, and the efficacy of active versus passive (i.e., natural regeneration) restoration remains unclear. We examined 11 indicators of forest structure, tree diversity and composition (adult and sapling), and aboveground carbon storage in 25 pairs of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…When compared with the tropical rainforests in the same region (Sinharaja undisturbed primary forest: 357.9 Mg ha −1 ), there is a high potential to sequester more carbon in our study site [43]. Likewise, an evaluation of the change in forest structure and AGB in forest restoration sites in Western Ghats, India found that forest restoration sites had 49.0-89.8 Mg ha −1 in comparison to the 287.6 Mg ha −1 reported from contiguous forests in the region [44].…”
Section: Restoration Of Floristics Diversity Abovegound Biomass and Canopy Coversupporting
confidence: 44%
“…When compared with the tropical rainforests in the same region (Sinharaja undisturbed primary forest: 357.9 Mg ha −1 ), there is a high potential to sequester more carbon in our study site [43]. Likewise, an evaluation of the change in forest structure and AGB in forest restoration sites in Western Ghats, India found that forest restoration sites had 49.0-89.8 Mg ha −1 in comparison to the 287.6 Mg ha −1 reported from contiguous forests in the region [44].…”
Section: Restoration Of Floristics Diversity Abovegound Biomass and Canopy Coversupporting
confidence: 44%
“…For example, incentive programs geared towards securing forest carbon stocks from deforestation and degradation are likely to extend protection for species‐rich remnants of mature forests, which are crucial for conservation in heavily fragmented and human‐dominated biodiversity hotspots such as the Atlantic Forest (Magnago et al., ) and the Western Ghats. Restoration of presently degraded forests for future carbon and biodiversity benefits by, for example, promoting spontaneous natural recovery (Matos et al., ), or active restoration of degraded forests (Osuri, Kasinathan, Siddhartha, Mudappa, & Raman, ), could also offer synergies for conservation and climate change mitigation in HDLs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in degraded rainforests in this landscape revealed that AR led to significantly better recovery in forest structure and carbon storage than through NR (Osuri et al, 2019). Correspondingly, we assess here whether rainforest birds respond better to AR than to NR (or passive restoration) when compared to bird communities…”
Section: Introductionmentioning
confidence: 90%
“…Naturally regenerating degraded tropical forests may, however, remain floristically species-poor (Tabarelli et al, 2008) or show poorer recovery, particularly when located in isolated forest fragments (Osuri et al, 2019). This may consequently affect recolonisation by fauna, an indicator of restoration success (Cross et al, 2020;Wortley et al, 2013), which can further affect vegetation recovery, such as through changes in seed dispersal by faunal vectors (Fraser et al, 2015).…”
Section: Introductionmentioning
confidence: 99%